Information goods vs. industrial goods: Cost structure and competition - Jones, Roy; Mendelson, H. (2011)
We study markets for information goods and find that they differ significantly from markets for traditional industrial goods. Markets for information goods in which products are vertically differentiated lack the segmentation inherent in markets for industrial goods. As a result, a monopoly will offer only a single product. Competition leads to highly concentrated information-good markets, with the leading firm behaving almost like a monopoly even with free entry and without network effects. We study how the structure of the firms' cost functions drives our results. © 2011 INFORMS.